A Multispecies Cluster of GES-5 Carbapenemase–Producing Enterobacterales Linked by a Geographically Disseminated Plasmid. (20th November 2019) - Ellington, Matthew J; Davies, Frances; Jauneikaite, Elita; Hopkins, Katie L; Turton, Jane F; Adams, George; Pavlu, Jiri; Innes, Andrew J; Eades, Christopher; Brannigan, Eimear T; Findlay, Jacqueline; White, Leila; et al.
Abstract: Background: Early and accurate treatment of infections due to carbapenem-resistant organisms is facilitated by rapid diagnostics, but rare resistance mechanisms can compromise detection. One year after a Guiana Extended-Spectrum (GES)-5 carbapenemase–positive Klebsiella oxytoca infection was identified by whole-genome sequencing (WGS; later found to be part of a cluster of 3 cases), a cluster of 11 patients with GES-5–positive K. oxytoca was identified over 18 weeks in the same hospital. Methods: Bacteria were identified by matrix-assisted laser desorption/ionization–time of flight mass spectrometry, antimicrobial susceptibility testing followed European Committee on Antimicrobial Susceptibility Testing guidelines. Ertapenem-resistant isolates were referred to Public Health England for characterization using polymerase chain reaction (PCR) detection of GES, pulsed-field gel electrophoresis (PFGE), and WGS for the second cluster. Results: The identification of the first GES-5 K. oxytoca isolate was delayed, being identified by WGS. Implementation of a GES-gene PCR informed the occurrence of the second cluster in real time. In contrast to PFGE, WGS phylogenetic analysis refuted an epidemiological link between the 2 clusters; it also suggested a cascade of patient-to-patient transmission in the later cluster. A novel GES-5–encoding plasmid was present in K. oxytoca, Escherichia coli, and Enterobacter cloacae isolates from unlinked patients within the same hospital group and in human and wastewater isolates from 3 hospitals elsewhere in the United Kingdom. Conclusions: Genomic sequencing revolutionized the epidemiological understanding of the clusters; it also underlined the risk of covert plasmid propagation in healthcare settings and revealed the national distribution of the resistance-encoding plasmid. Sequencing results also informed and led to the ongoing use of enhanced diagnostic tests for detecting carbapenemases locally and nationally. Abstract : Whole-genome sequencing informed the detection of active and previously missed hospital clusters of Klebsiella oxytoca with GES-5; modes of spread were reinterpreted and GES-5 plasmid was found to be widely disseminated in other species of bacteria at remote locations.